Quantification of Floristic Diversity and Current Status of Macrophytes in Katarmoni Beel, a Sacred Wetland, Kishanganj District, Bihar - Mukherjee, Sudeshna; Mandal, Sujit Kumar (International Journal of Scientific Research in Biological Sciences, 2023)
Aquatic macrophytes play a significant role in maintaining the aquatic ecosystem by providing shelter for aquatic organisms and lives of rural communities. But unfortunately very negligible effort is put forwarded for the conservation of these great resources. It may create major problem in new future. So the aim of the present investigation is the documenting of the floristic composition, study of the vegetation of aquatic macrophytes, from Katarmoni beel. Extensive field survey was conducted from November 2021 to April 2023 and the total of 20 macrophytic species were recorded belonging to 14 families. The dominant families were Cyperaceae with 4 sp. followed by Poaceae with 3 sp. and 2 sp. of Convolvulaceae. Some qualitative characters viz. frequency, density, abundance, RF, RD, RA and IVI were also evaluated. Pontederia showed the highest dominance whereas Cyperus haspan and Pogostemon stellatus showed the lowest dominance.